2015
DOI: 10.1093/mnras/stv086
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Lynx-Cancer void galaxies. – V. The extremely isolated galaxy UGC 4722

Abstract: We present a detailed study of the extremely isolated Sdm galaxy UGC 4722 (M B = −17.4) located in the nearby Lynx-Cancer void. UGC 4722 is a member of the catalogue of isolated galaxies, and has also been identified as one of the most isolated galaxies in the Local Supercluster. Optical images of the galaxy however show that it has a peculiar morphology with an elongated ∼14 kpc-long plume. New observations with the Russian 6-m telescope (BTA) and the Giant Metrewave Radio Telescope (GMRT) of the ionised and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Id09002536: An isolated galaxy. Chengalur et al (2015) identified a disturbed HI morphology and argued that the galaxy has suffered recent minor merger. Id09562849: A merging dwarf candidate Annibali et al (2016) Id10080227: A merger origin compact early-type galaxy Id10545418: Interacting pair studied in Local Volume TiNy Titan (Pearson et al 2016) Id11451711: Interacting dwarf galaxies in the outskirt of a group environment (Paudel et al 2013).…”
Section: Appendixmentioning
confidence: 99%
“…Id09002536: An isolated galaxy. Chengalur et al (2015) identified a disturbed HI morphology and argued that the galaxy has suffered recent minor merger. Id09562849: A merging dwarf candidate Annibali et al (2016) Id10080227: A merger origin compact early-type galaxy Id10545418: Interacting pair studied in Local Volume TiNy Titan (Pearson et al 2016) Id11451711: Interacting dwarf galaxies in the outskirt of a group environment (Paudel et al 2013).…”
Section: Appendixmentioning
confidence: 99%
“…Voids may contain groups of galaxies (like NGC 428 group, Egorova et al 2019), pairs and triplets (Chengalur & Pustilnik 2013;Pustilnik & Tepliakova 2011;Pustilnik et al 2019), interacting and merging systems (Chengalur et al 2017;Beygu et al 2013). In particular, Chengalur et al (2015) investigated another void galaxy UGC 4722 that was considered to be one of the most isolated galaxies in the Local Supercluster, though revealing the peculiar morphology. Authors conclude that actually it is a merging system, and the second component, a very gas-rich dwarf, was almost completely destroyed.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Several studies have shown that a number of star-forming dwarf galaxies present filamentary H i and/or extended structures, which may indicate a recent cold gas infall/accretion (e.g. Chengalur et al 2015). In this sense, the extended structure of this galaxy could be a remnant of one of these processes.…”
Section: Tidal Interactions Mergers And/or Gas Infallmentioning
confidence: 94%